Implementasi Gerakan Literasi Sekolah Bagi Anak Tunarungu Kelas VII di SLB Negeri 1 Painan - Welly Manovy; Asep Ahmad Sopandi (Universitas Negeri Padang, 2020)
This study discusses the problems found in SLB Negeri 1 Painan regarding the implementation of the school literacy movement. This study aims to learn how to apply the school literacy movement for deaf children of class VII in SLB Negeri 1 Painan. The method used is descriptive qualitative, research subjects are school principals, class teachers, librarians, students and parents of students. Data collected through observation, interviews and documentation obtained are then analyzed and presented by drawing conclusions about the meaning of the data collected. Strategies in the school literacy movement prioritize effective social environments as a model of communication and literacy-friendly environmental conditions. Implementation starts from coaching training towards development and learning training. The benefits of applying the literacy movement can be felt by principals, class teachers, librarians, students and parents of students. SLB Negeri 1 Painan.